Time to chill out: a do-it-yourself guide to swim tapering - Kostich, A.
No three words in the endurance athlete's vocabulary inspire such joy and excitement as the three above. Tapering is the icing on the cake after a season of hard training: the gradual easing-up of intensity and distance in one's workouts in anticipation of a big race. Timing a taper to align with a personal best performance is a difficult and nerve-wracking task, requiring discipline and a certain amount of restraint (not something endurance athletes are known for!). A swimmer's taper is different than a runners or cyclists in that there is a lot more involved than a decrease in distance per workout. Sprinting, long easy swimming, pulling with partial or full gear, and delicate changes in daily yardage are all components of a successful taper, and even some of the most talented swimmers have trouble with the timing and execution of such a precise plan. While each swimmers taper is a deeply personal and unique thing, what follows is a general guideline for a do-it-yourself taper and what you can do on your own if you dont have a coach to help guide you along. A taper can last anywhere from one to four weeks. Anything less would be considered a few days' rest, and anything more would be pushing your luck in terms of maintaining your peak conditioning. Since no two swimmers are alike, there is no fixed way to taper, but a good place to start is to model your yardage after the 100:75:50 rule. That is, if a full workout for you is 4,000 yards, then the first week you taper 75 percent of that distance, or 3,000 yards. The next week you taper 50 percent of your full workouts, or 2,000 yards. So the 100:75:50 taper is a two-week taper where you skim down the length of your swims to half of what you were covering initially. If you are a sprinter who doesnt train heavy yardage, you may only want to taper a week at 100:75. If you are a distance swimmer who gets really broken down with long workouts and challenging sets throughout the season, you may want to take a more luxurious taper of 100:75:66:50, a three-week taper. Remember, this is a personal thing, and each of you may find that your peak-conditioning needs differ from the swimmer in the next lane. It may take you a few tries at a taper to determine what is best for you. In addition to decreasing yardage, it is important to allow your body a chance to rest and recover from the beating it has taken all season in the midst of your training. You may begin this process by giving yourself more rest during interval training, and listening to your body at each turn. If your muscles are sore, you should not be sprinting or practicing pace sets until you feel fresh and energetic. If you feel lethargic a week into your taper, allow yourself a day off completely. Get lots of sleep. Watch what you eat since you are easing up on your training intensity. Under no circumstances should you be in the weight room for the month before your race, even if you have been on a consistent weightlifting program. Toward the end of your taper you should be sprinting only a few timed sprints at the end of an easy workout, say 4x25 s and maybe a 50. Your times for these sprints should be a lot faster than in midseason if you are executing your taper correctly. If they are not, you need more rest. As a distance swimmer, you should be doing only 3 to 5 x 100 s pace and it should feel easy and sustainable. Take plenty of time to swim down after these end-of-workout drills, and you may exit the water only when your heart rate is down to normal active rest. Taper workouts can involve lots of easy swimming, drills, kicking sets to loosen your legs, and pulling sets with buoy and paddles (do not use a tube as it adds unnecessary weight). Warm-up can be twice as long as your usual warm-up routine, and swim down should be twice as long as well. That may not leave much yardage for anything else, which is why most tapers can seem like little more than a warm-up and a swim down! The point is to enjoy the opportunity to recover and feel good in the water and put your hard training behind you in preparation for your big race. Here is a sample taper workout based on someone who normally trains 3,000 to 4,000 yards a day: 800 warm up 200 kick 400 pull (buoy and paddles) 3x100 s pace @ 10 secs rest (for a distance swimmer) or 1x50, 2x25 s @ 1:00 rest (for a sprinter) 300 swim down TOTAL: 2,000 yards During the last week of your taper, you should not need to take a complete day off because you should start feeling fast and smooth in the water. If not, swim easy until your muscles are warmed up, and get out. Try again the next day. Sometimes your body isnt used to all the rest it is getting, and as a result you'll feel restless during your bedtime. You may also feel awkward in the water, but dont worry; you do not have to feel terrific until the day you race! 'Rest' assured Tapering also has a mental advantage: You should take the time to enjoy the benefits of 'resting on your laurels' and relax, fully confident that you have done everything necessary to prepare for your race. The hard work is behind you! Endurance athletes have been known to stress during taper time because their work ethic is such that they can not allow themselves the physical break that a taper requires. As a result, they continue training too hard, or they psyche themselves out by fearing losing shape with the rest they are taking. Even a monthlong taper will not hurt your conditioning if you are an endurance athlete, so 'rest' assured!